Analisis Yuridis Penyelesaian Sengketa Konsumen atas Wanprestasi Developer Terhadap Perjanjian Kredit Ruko oleh BPSK WKP II Banten Berdasarkan UU No. 8 Tahun 1999 tentang Perlindungan Konsumen: Juridical Analysis of Consumer Dispute Resolution Regarding Developer's Breach of Contract in Shop-House Construction Credit Agreements by BPSK WKP II Banten Based on Law Number 8 of 1999 Concerning Consumer Protection - Muflihah Muflihah (Jurnal Hukum Lex Generalis, 2025)
This agreement essentially constitutes a sale of services that binds the parties to fulfill their obligations in accordance with the terms of the contract. However, in practice, discrepancies in the contract terms occur, resulting in a breach of contract, primarily by the Developer. Common forms of breach include delays in construction and building specifications that do not conform to the agreement. A concrete case occurred between Iin Sulhiah and PT. Graha Artha Kencana, which was reported to the Consumer Dispute Settlement Body (BPSK) WKP II Banten for alleged breach of contract. The purpose of this study is to understand the dispute resolution mechanism for consumer complaints regarding Developer’s breach of contract in the shop-house credit agreement handled by BPSK WKP II Banten, and to examine the responsibility of the business actor to the harmed consumer based on Law Number 8 of 1999 concerning Consumer Protection. The research method used is normative legal research with a juridical normative approach. In this study, the researcher uses statute approach and case approach. The researcher also uses primary legal materials obtained through interviews, secondary legal materials from literature, and tertiary legal materials. Data collection techniques used in this research include literature study and qualitative descriptive data analysis. The research results conclude that consumer dispute resolution regarding the developer's breach of contract in a shop-house (ruko) credit agreement through non-litigation at BPSK (Consumer Dispute Settlement Agency) by means of mediation has proven to be ineffective. This is because no agreement was reached between the parties during the hearing process. Therefore, a more effective resolution is through arbitration, namely by fully submitting the dispute resolution to BPSK to be decided by the Panel, thereby allowing an agreement to be reached between both parties. Business actors are held responsible for breaches of contract in standard agreements that cause harm to consumers. In accordance with Law Number 8 of 1999 concerning Consumer Protection, there is legal accountability imposed on business actors.